Method for preparing ZrSiO4 aerogel by combining sol-gel with supercritical drying
By combining the sol-gel method with CO2 supercritical drying process, the problems of low operating temperature and poor thermal stability of ZrSiO4 aerogel were solved, and a high porosity, low density and high temperature resistant ZrSiO4 aerogel was prepared, which is suitable for aerospace thermal protection and high temperature insulation.
Patent Information
- Application Number
- CN202511429546.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-09
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2045-10-09
AI Technical Summary
Existing ZrSiO4 aerogels have low operating temperatures and poor long-term thermal stability, making it difficult to meet the application requirements of aerospace thermal protection and high-temperature insulation.
By employing the sol-gel method combined with CO2 supercritical drying, and by selecting appropriate silicon sources, zirconium sources, and crosslinking agents, and by designing raw material components, controlling the gelation process, and controlling heat treatment conditions, an aerogel with ZrSiO4 as the main component was prepared.
A ZrSiO4 aerogel with high porosity, low density, good high temperature resistance and long-term thermal stability was prepared. It can be used at temperatures above 1500 ℃ and has excellent thermal insulation and thermal shock resistance properties.
Smart Images

Figure CN120903557A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The technical scheme of the present application provides a method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, and belongs to the field of heat insulation material preparation. BACKGROUND
[0002] For applications in extreme thermal environments, such as thermal protection structures of spacecraft and military vehicles, heat insulation structures of industrial high-temperature equipment, etc., the material needs to meet the requirements of light weight, ultra-low thermal conductivity, high thermal stability, excellent mechanical properties, etc. at the same time. Although traditional ceramic aerogels have extremely low thermal conductivity due to their nano-porous structure, their inherent brittleness leads to low compression strain, making them difficult to withstand mechanical impact or thermal stress and prone to cracking failure. At high temperatures, they are prone to structure collapse due to crystallization and powdering, losing the heat insulation function. Existing reinforcement methods, such as fiber doping, can improve the mechanical resilience, but often lead to an increase in thermal conductivity. Traditional preparation processes such as precipitation and hydrothermal method have poor structure controllability and single fiber orientation, making it difficult to mass-produce complex three-dimensional components, limiting the application of traditional ceramic aerogels in heat insulation of special-shaped parts. Therefore, it is of great significance to develop new ceramic aerogels with ultra-light, high-elastic, heat insulation, and excellent high-temperature stability, and to realize their structure design and performance control for large-scale production to meet the needs of efficient thermal protection in extreme environments.
[0003] Aerogel is a low-density porous solid material composed of nanoparticles or polymer molecules aggregated with each other, having high porosity and large internal surface area. The preparation method of aerogel is usually to first prepare a gel through chemical reaction, and then to obtain aerogel through drying. Sol-gel method is a common method for preparing aerogel, but the pores of wet gel are prone to collapse during drying due to the action of capillary force, leading to the fragmentation of dry gel. However, supercritical drying can avoid the action of capillary force and obtain aerogel with complete structure. Organic solvent supercritical drying reaches and maintains the supercritical state of organic solvent without crossing the liquid-gas phase boundary, and then reduces the pressure to ambient pressure at constant temperature to achieve the purpose of drying, but the process of reaching the supercritical state may damage the structure of the gel. The critical conditions of CO2 (31 ℃ and 74 bar) are more moderate than those of organic solvents such as ethanol (241.3 ℃ and 61 bar) and acetone (235 ℃ and 47 bar), causing less change in gel structure. CO2 supercritical drying combined with sol-gel process is a common method for preparing aerogel.
[0004] ZrSiO4 is a high-temperature structural ceramic material with a melting point of more than 2400 ℃, excellent chemical stability, low thermal expansion coefficient and low thermal conductivity. As an advanced ceramic material with high-temperature stability and good mechanical properties, its high melting point and oxidation resistance make it possible to realize the realization of aerogel materials in extreme environments. Zirconium silicate ceramic is prepared into aerogel, which is expected to obtain aerogel materials with low density, high elasticity, high flexibility, high thermal stability and high thermal insulation, etc., to overcome the shortcomings of traditional ceramic aerogel such as high brittleness, easy pulverization and poor high-temperature stability, so as to better meet the needs of high-efficiency thermal protection in extreme environments.
[0005] At present, ZrSiO4 aerogel cannot be applied in the fields of aerospace thermal protection and high-temperature thermal insulation due to its low use temperature (below 1200 ℃) and poor long-term thermal stability. In previous studies, sol-gel method or electrospinning method was mostly used, and then combined with medium-low temperature heat treatment process or non-heat treatment process to prepare ZrSiO4 aerogel. In order to retain the performance of high porosity and high specific surface area of aerogel, the high-temperature resistance of aerogel is usually sacrificed. The phase composition of ZrSiO4 aerogel prepared in previous studies is mainly SiO2, ZrO2 and a small amount of ZrSiO4, which will produce crystallization, sintering and other phenomena at extremely high temperature, resulting in performance degradation. Therefore, it is of great significance to prepare ZrSiO4 aerogel with high porosity, low density, high-temperature resistance and good long-term thermal stability for its application in the fields of aerospace thermal protection and high-temperature thermal insulation. SUMMARY
[0006] The purpose of the present application is to provide a preparation method of high-temperature-resistant ZrSiO4 aerogel, which solves the problems of low use temperature and poor long-term thermal stability of existing ZrSiO4 aerogel. In previous studies, medium-low temperature sintering process leads to low ZrSiO4 content in ZrSiO4 aerogel and low limit use temperature. The present application adopts high-temperature sintering process, and the phase composition of the prepared aerogel is mainly ZrSiO4, and the use temperature can reach more than 1500 ℃. The ZrSiO4 aerogel prepared by the present application significantly improves the thermal stability, high-temperature resistance and ablation resistance of the material while reducing the cost. It provides a new idea and scheme for the application of ZrSiO4 aerogel in the fields of thermal protection and high-temperature thermal insulation.
[0007] The technical scheme of the present application adopts sol-gel method combined with supercritical drying process to prepare ZrSiO4 aerogel. Zirconium oxy salt or alkoxide is used as zirconium source; organic silane precursor or inorganic silicon compound is used as silicon source; acid, base or organic compound is used as crosslinking agent; the zirconium source, silicon source and crosslinking agent are mixed and gelled at a certain temperature, and then the gel is subjected to CO2 supercritical drying to obtain dry gel, and the dry gel is converted into ZrSiO4 aerogel through heat treatment.
[0008] Compared with the prior art, the technical scheme of the present application solves the problems of the prior method, i.e., difficulty in preparing ZrSiO4 aerogel, low use temperature (below 1200 ℃) and poor long-term thermal stability, by selecting appropriate silicon source, zirconium source and crosslinking agent, and by designing raw material components, controlling gelation process, designing supercritical drying and heat treatment conditions, and high-porosity, low-density, high-temperature-resistant and long-term-thermal-stable ZrSiO4 aerogel is obtained. The implementation of the technology provides a new idea and scheme for the research and development of high-temperature insulation ZrSiO4 aerogel material, and can further improve the use temperature range of high-temperature aerogel material.
[0009] The present application is a method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, which is carried out according to the following steps: (1) Dissolve the crosslinking agent in a mixed solution of anhydrous ethanol and deionized water, and stir to mix uniformly; the crosslinking agent is one or more of malic acid, tartaric acid, polymaleic acid, polyacrylic acid, hexamethylenetetramine, formamide, polyethyleneimine, propylene oxide, polyvinyl alcohol and sodium carboxymethyl cellulose; the volume ratio of anhydrous ethanol to deionized water is 0.01:1 to 1:0.01; (2) Add the silicon source and zirconium source to the mixed solution containing the crosslinking agent, and stir to form a precursor solution; the temperature range for stirring the raw materials is 1-80 ℃, and the stirring time is 0.1-24 h; the silicon source is one or more of tetraethyl orthosilicate, dimethyldiethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, γ-aminopropyltriethoxysilane, silica sol and sodium silicate; the zirconium source is one or more of zirconium oxychloride, zirconium oxynitrate, zirconium n-butylate, zirconium acetate, zirconium sulfate and zirconium isopropylate; the concentration ratio of the silicon source, the zirconium source and the crosslinking agent in the raw materials is 1.0-2.0:1.0-2.0:0.01-4.0; (3) Gel the precursor solution in an oven, the gelation temperature is 30-90 ℃, and the gelation time is 0.5-72 h; the obtained wet gel is soaked in ethanol for 24-72 h; (4) Put the obtained wet gel into a CO2 supercritical drying reaction kettle, maintain the temperature in the reaction kettle at 4 ℃, and replace with liquid CO2 for 0.5-72 h; increase the temperature in the reaction kettle to make CO2 reach the supercritical state, maintain for 0.1-24 h, then depressurize and take out the dried gel; (5) Put the dried gel into a muffle furnace for high-temperature heat treatment, the heat treatment temperature is 1000-1600 ℃, the heating rate is 1-5 ℃ / min, the holding time is 0.5-12 h, and the cooling rate is 1-5 ℃ / min, to obtain ZrSiO4 aerogel.
[0010] The advantages of the present application over the prior art are as follows: First, a suitable silicon source and zirconium source are co-hydrolyzed at low temperature, and the sol stability is dynamically regulated by a crosslinking agent to form a uniform precursor network, which realizes uniform mixing of the silicon source and the zirconium source, is conducive to uniform subsequent reaction and avoids the generation of impurity phases.
[0011] Second, under CO2 supercritical conditions, the gel maintains high porosity, low density and an intact gel network after the drying process; after heat treatment at 1000-1600 ℃, ZrO2 and SiO2 are efficiently reacted to generate ZrSiO4, and ZrSiO4 aerogels with high porosity, low density, good high-temperature resistance and good long-term thermal stability are obtained.
[0012] Third, the present application solves the problems of low ZrSiO4 content, low use temperature and poor long-term thermal stability in the preparation of ZrSiO4 aerogels. BRIEF DESCRIPTION OF DRAWINGS
[0013] Figure 1 A physical map of the ZrSiO4 aerogel prepared in Example 1; Figure 2 An XRD map of the ZrSiO4 aerogel prepared in Example 1; Figure 3 A physical map of the ZrSiO4 aerogel prepared in Example 2; Figure 4 An XRD map of the ZrSiO4 aerogel prepared in Example 2; Figure 5 An SEM map of the ZrSiO4 aerogel prepared in Example 3. DETAILED DESCRIPTION
[0014] The present application will be further described in conjunction with the examples. However, the scope of the present application is not limited to the following examples. Those skilled in the art can understand that various changes and modifications can be made to the present application without departing from the spirit and scope of the present application.
[0015] The instruments, reagents and materials involved in the following examples, if not specifically stated, are conventional instruments, reagents and materials already existing in the prior art, which can be obtained through regular commercial channels. The experimental methods and detection methods involved in the following examples, if not specifically stated, are conventional experimental methods and detection methods already existing in the prior art.
[0016] Example 1 A method for preparing ZrSiO4 aerogels by sol-gel combined with supercritical drying, comprising the following steps: (1) First, dissolve 0.2 g of malic acid in a mixed solution of anhydrous ethanol and deionized water and stir evenly on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 1:1. (2) Tetraethyl orthosilicate and zirconium oxychloride were added to a mixed solution containing a crosslinking agent and stirred until homogeneous to form a precursor solution; the solution was placed in a 20 ℃ water bath and stirred for 20 h; the tetraethyl orthosilicate, zirconium oxychloride and malic acid were in a concentration ratio of 1:1:0.1; (3) Place the mixed solution in an oven at 20 °C, gel for 60 h, and then soak it in ethanol for 60 h; (4) The obtained wet gel was placed in a CO2 supercritical drying reactor and the temperature inside the reactor was maintained at 4 ℃. Liquid CO2 was used to replace the gel for 60 h. The temperature inside the reactor was raised to 40 ℃ and held for 2 h after reaching the supercritical state. Then the pressure was released and the dried gel was taken out. (5) The supercritical dried sample was placed in a muffle furnace and heated to 1000 °C at a rate of 1 °C / min in an air atmosphere, and held at that temperature for 12 h. After cooling to room temperature, a ZrSiO4 aerogel with high porosity, low density, good high temperature resistance and good long-term thermal stability was obtained. The physical image and XRD pattern of the ZrSiO4 aerogel prepared in this example are attached. Figure 1 and 2 As shown, the aerogel has a high ZrSiO4 phase content; the ZrSiO4 aerogel prepared in this example has a porosity of 96.8% and a density of 0.1459 g / cm³. 3 The pore volume is 1.68 cm³. 3 / g, specific surface area 90.6 m² 2 / g, compressive strength 2.75 MPa, compressive strain 7.0%, thermal conductivity 0.039 W·m -1 K -1 After calcination at 1500 ℃ for 2 hours, slight agglomeration occurred, but the pore structure remained largely intact, and the ZrSiO4 aerogel showed no decomposition. After one side of the ZrSiO4 aerogel was subjected to intense heating with a butane torch flame (>1300 ℃) for 5 minutes, the temperature on the other side of the ZrSiO4 aerogel stabilized below 50 ℃, indicating that the ZrSiO4 aerogel prepared in Example 1 has excellent thermal insulation properties. The sample was first rapidly heated to 1000 ℃ and then rapidly cooled to ambient temperature (room temperature), with a temperature change rate as high as 200 ℃ / min. After 30 high-temperature thermal shock cycles, the overall structure of the aerogel maintained its original morphology, indicating that the ZrSiO4 aerogel prepared in Example 1 has excellent thermal shock resistance.
[0017] Example 2 A method for preparing ZrSiO4 aerogel by sol-gel combined supercritical drying, comprising the following steps: (1) First, 0.1 g of tartaric acid is dissolved in a mixed solution of anhydrous ethanol and deionized water, and stirred uniformly on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 0.01:1; (2) Dimethyldiethoxysilane and zirconyl nitrate are added to the mixed solution containing the crosslinking agent, and stirred uniformly to form a precursor solution; the solution is placed in a 30℃ water bath for stirring for 24 h; the concentration ratio of dimethyldiethoxysilane, zirconyl nitrate and tartaric acid is 1:1:0.01; (3) The mixed solution is placed in a 30℃ oven, and after 70 h of gelation, it is soaked in ethanol for 70 h; (4) The obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4℃, and liquid CO2 is used for replacement for 60 h; the temperature in the reaction kettle is increased to 40℃, and after reaching the supercritical state, it is maintained for 12 h, then the pressure is released and the dried gel is taken out; (5) The sample after supercritical drying is placed in a muffle furnace, and heated to 1100℃ at a rate of 2℃ / min in an air atmosphere, and maintained for 6 h; after cooling to room temperature, ZrSiO4 aerogel with high porosity, low density, good high-temperature performance and long-term thermal stability is obtained, and the actual object diagram and XRD diagram of the ZrSiO4 aerogel prepared in this embodiment are shown in Figs. Figure 3 and 4 , and the ZrSiO4 phase content in the aerogel is high; the porosity of the ZrSiO4 aerogel prepared in this embodiment is 97.8%, the density is 0.1003 g / cm 3 , the pore volume is 1.72 cm 3 / g, the specific surface area is 87.2 m 2 / g, the compressive strength is 2.98 MPa, the compressive strain is 6.7%, and the thermal conductivity is 0.033 W·m -1 K -1 ; after 2 hours of high-temperature calcination at 1500℃, slight agglomeration occurs, the pore structure is basically maintained, and the ZrSiO4 aerogel does not decompose; after the one side of the ZrSiO4 aerogel is heated by a butane torch flame (>1300℃) for 5 minutes, the temperature on the other side of the ZrSiO4 aerogel is stabilized below 60℃, indicating that the ZrSiO4 aerogel prepared in Example 2 has excellent heat insulation performance; the sample is rapidly heated to 1100℃, and then cooled to ambient temperature (room temperature), and the temperature change rate is as high as 220℃ / min; after 35 cycles of high-temperature thermal shock, the overall structure of the aerogel maintains the original form, indicating that the ZrSiO4 aerogel prepared in Example 2 has excellent thermal shock resistance.
[0018] Example 3 A method for preparing ZrSiO4 aerogel using a sol-gel combination and supercritical drying includes the following steps: (1) First, dissolve 0.3 g of polymaleic acid in a mixed solution of anhydrous ethanol and deionized water, and stir evenly on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 0.5:1. (2) Add methyltrimethoxysilane and zirconium n-butoxide to a mixed solution containing a crosslinking agent and stir until homogeneous to form a precursor solution; place the solution in a 40 ℃ water bath and stir for 12 h; the concentration ratio of methyltrimethoxysilane, zirconium n-butoxide and polymaleic acid is 1:1:0.5. (3) Place the mixed solution in an oven at 40 °C, gel for 72 h, and then soak it in ethanol for 72 h. (4) The obtained wet gel was placed in a CO2 supercritical drying reactor and the temperature inside the reactor was maintained at 4 ℃. Liquid CO2 was used to replace the gel for 60 h. The temperature inside the reactor was raised to 40 ℃ and maintained for 18 h after reaching the supercritical state. Then the pressure was released and the dried gel was taken out. (5) The supercritical dried sample was placed in a muffle furnace and heated to 1300 °C at a rate of 3 °C / min in an air atmosphere, and held at that temperature for 12 h. After cooling to room temperature, a ZrSiO4 aerogel with high porosity, low density, good high temperature resistance and good long-term thermal stability was obtained. The ZrSiO4 phase content in the aerogel was high. The SEM images of the ZrSiO4 aerogel prepared in this example are attached. Figure 5 As shown, the ZrSiO4 aerogel prepared in this embodiment has a porosity of 96.6% and a density of 0.1550 g / cm³. 3 The pore volume is 1.69 cm³. 3 / g, specific surface area 98.2 m² 2 / g, compressive strength 2.21 MPa, compressive strain 5.9%, thermal conductivity 0.036 W·m -1 K -1 After calcination at 1500 ℃ for 2 hours, slight agglomeration occurred, but the pore structure remained largely intact, and the ZrSiO4 aerogel showed no decomposition. After one side of the ZrSiO4 aerogel was subjected to intense heating with a butane torch flame (>1300 ℃) for 5 minutes, the temperature on the other side of the ZrSiO4 aerogel stabilized below 70 ℃, indicating the excellent thermal insulation performance of the ZrSiO4 aerogel prepared in Example 3. The sample was first rapidly heated to 1300 ℃ and then cooled to ambient temperature (room temperature), with a temperature change rate as high as 250 ℃ / min. After 40 high-temperature thermal shock cycles, the overall structure of the aerogel maintained its original morphology, indicating the excellent thermal shock resistance of the ZrSiO4 aerogel prepared in Example 3.
[0019] Example 4 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, 0.1 g of polyacrylic acid is dissolved in a mixed solution of anhydrous ethanol and deionized water, and stirred uniformly on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 1:0.6; (2) Methyltrimethoxysilane and zirconyl nitrate are added to the mixed solution containing the crosslinking agent, and stirred uniformly to form a precursor solution; the solution is placed in a 40 ℃ water bath for stirring for 18 h; the concentration ratio of methyltrimethoxysilane, zirconyl nitrate and polyacrylic acid is 1:1.5:1; (3) The mixed solution is placed in a 40 ℃ oven, and after gelation for 24 h, it is soaked in ethanol for 24 h; (4) The obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4 ℃, and liquid CO2 is used for replacement for 36 h; the temperature in the reaction kettle is increased to 35 ℃, and when the supercritical state is reached, it is maintained for 0.7 h, then the pressure is released and the dried gel is taken out; (5) The sample after supercritical drying is placed in a muffle furnace, and heated to 1500 ℃ at a rate of 2 ℃ / min in an air atmosphere, and maintained for 3 h; after cooling to room temperature, a ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability is obtained, and the ZrSiO4 phase content in the aerogel is high; the ZrSiO4 aerogel prepared in this example has a porosity of 96.6%, a density of 0.1550 g / cm 3 , a pore volume of 1.45 cm 3 / g, a specific surface area of 69.3 m 2 / g, a compressive strength of 2.19 MPa, a compressive strain of 7.9%, and a thermal conductivity of 0.042 W·m -1 K -1 ; after 2 hours of high-temperature calcination at 1500 ℃, slight agglomeration occurs, the pore structure is basically maintained, and the ZrSiO4 aerogel does not decompose; after the ZrSiO4 aerogel is heated by a butane torch flame (>1300 ℃) on one side for 5 minutes, the temperature on the other side of the ZrSiO4 aerogel stabilizes below 65 ℃, indicating that the ZrSiO4 aerogel prepared in Example 4 has excellent heat insulation performance; the sample is first rapidly heated to 1500 ℃, and then cooled to ambient temperature (room temperature), and the temperature change rate is as high as 300 ℃ / min; after 45 cycles of high-temperature thermal shock, the overall structure of the aerogel remains the original form, indicating that the ZrSiO4 aerogel prepared in Example 4 has excellent thermal shock resistance.
[0020] Example 5 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, 0.1 g of hexamethylene tetramine is dissolved in a mixed solution of anhydrous ethanol and deionized water, and stirred uniformly on a magnetic stirrer; the volume ratio of anhydrous ethanol and deionized water is 0.2:1; (2) γ-aminopropyl triethoxysilane and zirconium sulfate are added to the mixed solution containing the crosslinking agent to form a precursor solution after uniform stirring; the solution is placed in a 80 ℃ water bath for stirring for 0.5 h; the concentration ratio of methyltrimethoxysilane, zirconyl nitrate and polyacrylic acid is 2:1:0.01; (3) The mixed solution is placed in a 55 ℃ oven, and after gelation for 50 h, it is soaked in ethanol for 24 h; (4) The obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4 ℃, and liquid CO2 is used for replacement for 24 h; the temperature in the reaction kettle is increased to 40 ℃, and after reaching the supercritical state, it is maintained for 1 h, then the pressure is released and the dried gel is taken out; (5) The sample after supercritical drying is placed in a muffle furnace, and heated to 1400 ℃ at a rate of 4 ℃ / min in an air atmosphere, and maintained for 3 h; after cooling to room temperature, ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability is obtained; the porosity of the ZrSiO4 aerogel prepared in this example is 96.2%, and the density is 0.1733 g / cm 3 .
[0021] Example 6 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, 0.1 g of formamide is dissolved in a mixed solution of anhydrous ethanol and deionized water, and stirred uniformly on a magnetic stirrer; the volume ratio of anhydrous ethanol and deionized water is 0.6:1; (2) Sodium silicate and zirconium acetate are added to the mixed solution containing the crosslinking agent to form a precursor solution after uniform stirring; the solution is placed in a 10 ℃ water bath for stirring for 6 h; the concentration ratio of sodium silicate, zirconium acetate and formamide is 2:2:0.01; (3) The mixed solution is placed in a 50 ℃ oven, and after gelation for 36 h, it is soaked in ethanol for 60 h; (4) The obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4 ℃, and liquid CO2 is used for replacement for 8 h; the temperature in the reaction kettle is increased to 40 ℃, and after reaching the supercritical state, it is maintained for 0.5 h, then the pressure is released and the dried gel is taken out; (5) The supercritical dried sample is placed in a muffle furnace, and heated to 1600 ℃ at a rate of 2 ℃ / min under air atmosphere, and kept for 1 h; cooled to room temperature to obtain ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability; the porosity of the ZrSiO4 aerogel prepared in the embodiment is 93.8%, and the density is 0.2827 g / cm 3 .
[0022] Example 7 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, 0.1 g of polyethyleneimine is dissolved in a mixed solution of anhydrous ethanol and deionized water, and uniformly stirred on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 1:0.2; (2) Silicon sol and zirconium oxychloride are added to the mixed solution containing the crosslinking agent, and stirred uniformly to form a precursor solution; the solution is placed in a 50 ℃ water bath for stirring for 8 h; the concentration ratio of silicon sol, zirconium oxychloride and polyethyleneimine is 1:1:1.5; (3) The mixed solution is placed in a 35 ℃ oven, and gelled for 12 h, and then soaked in ethanol for 20 h; (4) The obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4 ℃, and liquid CO2 is used to replace for 48 h; the temperature in the reaction kettle is increased to 40 ℃, and when the supercritical state is reached, it is kept for 0.5 h, and then the dried gel is taken out; (5) The supercritical dried sample is placed in a muffle furnace, and heated to 1150 ℃ at a rate of 3 ℃ / min under air atmosphere, and kept for 10 h; cooled to room temperature to obtain ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability; the porosity of the ZrSiO4 aerogel prepared in the embodiment is 95.5%, and the density is 0.2025 g / cm 3 .
[0023] Example 8 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, 0.1 g of propylene oxide is dissolved in a mixed solution of anhydrous ethanol and deionized water, and uniformly stirred on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 0.8:1; (2) Tetraethyl orthosilicate and zirconium sulfate are added to the mixed solution containing the crosslinking agent, and stirred uniformly to form a precursor solution; the solution is placed in a 45 ℃ water bath for stirring for 8 h; the concentration ratio of tetraethyl orthosilicate, zirconium sulfate and propylene oxide is 2:2:4; (3) Put the mixed solution into an oven at 60 ℃, and immerse the gel in ethanol after 24 h of gelation for 48 h; (4) Put the obtained wet gel into a CO2 supercritical drying reaction kettle, maintain the temperature in the reaction kettle at 4 ℃, and replace with liquid CO2 for 72 h; increase the temperature in the reaction kettle to 40 ℃, and keep it at this temperature for 0.5 h after reaching the supercritical state, then release the pressure and take out the dried gel; (5) Put the sample after supercritical drying into a muffle furnace, heat to 1600 ℃ at a rate of 3 ℃ / min under air atmosphere, and keep it at this temperature for 0.5 h; cool to room temperature to obtain ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability; the ZrSiO4 aerogel prepared in this example has a porosity of 93.6% and a density of 0.2918 g / cm 3 .
[0024] Example 9 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, dissolve 0.1 g of polyvinyl alcohol in a mixed solution of anhydrous ethanol and deionized water, and uniformly stir on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 1:0.1; (2) Add sodium silicate and zirconyl nitrate to the mixed solution containing the crosslinking agent, and stir uniformly to form a precursor solution; place the solution in a 45 ℃ water bath and stir for 8 h; the concentration ratio of sodium silicate, zirconyl nitrate and polyvinyl alcohol is 1:2:1.2; (3) Put the mixed solution into an oven at 50 ℃, and immerse the gel in ethanol after 36 h of gelation for 60 h; (4) Put the obtained wet gel into a CO2 supercritical drying reaction kettle, maintain the temperature in the reaction kettle at 4 ℃, and replace with liquid CO2 for 72 h; increase the temperature in the reaction kettle to 40 ℃, and keep it at this temperature for 0.6 h after reaching the supercritical state, then release the pressure and take out the dried gel; (5) Put the sample after supercritical drying into a muffle furnace, heat to 1100 ℃ at a rate of 3 ℃ / min under air atmosphere, and keep it at this temperature for 10 h; cool to room temperature to obtain ZrSiO4 aerogel with high porosity, low density, good high-temperature resistance and long-term thermal stability; the ZrSiO4 aerogel prepared in this example has a porosity of 95.9% and a density of 0.1869 g / cm 3 .
[0025] Example 10 A method for preparing ZrSiO4 aerogel by sol-gel combined with supercritical drying, comprising the following steps: (1) First, dissolve 0.1 g of sodium carboxymethyl cellulose in a mixed solution of anhydrous ethanol and deionized water, and stir evenly on a magnetic stirrer; the volume ratio of anhydrous ethanol to deionized water is 1:0.2. (2) Add methyltrimethoxysilane and zirconium sulfate to a mixed solution containing a crosslinking agent, and stir until homogeneous to form a precursor solution; place the solution in a 50 ℃ water bath and stir for 12 h; sodium silicate, zirconium oxynitrate, and polyvinyl alcohol are added in a concentration ratio of 2:1:1.2; (3) Place the mixed solution in an oven at 60 °C, gel for 24 h, and then soak it in ethanol for 72 h. (4) The obtained wet gel was placed in a CO2 supercritical drying reactor and the temperature inside the reactor was maintained at 4 ℃. Liquid CO2 was used to replace the gel for 72 h. The temperature inside the reactor was raised to 40 ℃ and held for 0.8 h after reaching the supercritical state. Then the pressure was released and the dried gel was taken out. (5) The supercritical dried sample was placed in a muffle furnace and heated to 1500 °C at a rate of 5 °C / min in air atmosphere, and held at that temperature for 12 h; after cooling to room temperature, a ZrSiO4 aerogel with high porosity, low density, good high temperature resistance and good long-term thermal stability was obtained; the ZrSiO4 aerogel prepared in this example had a porosity of 96.9% and a density of 0.1414 g / cm³. 3 .
[0026] Comparative Example 1 Unlike Example 1, in step (5), the temperature was increased to 1550 °C at a rate of 10 °C / min and held for 15 h in an air atmosphere inside a muffle furnace, while the other experimental conditions remained the same; the product prepared in this comparative example had a porosity of 82.5% and a density of 0.795 g / cm³. 3 The pore volume is 1.01 cm³. 3 / g, specific surface area 30.6 m² 2 / g, compressive strength 1.51 MPa, thermal conductivity 0.25 W·m -1 K -1 .
[0027] Comparative Example 2 Unlike Example 2, in step (2), the concentration ratio of dimethyldiethoxysilane, zirconium oxynitrate, and tartaric acid was 1:1:8, while the other experimental conditions remained the same. The product prepared in this comparative example had a porosity of 71.5% and a density of 1.23 g / cm³. 3 The pore volume is 0.98 cm³. 3 / g, specific surface area 20.6 m² 2 / g, compressive strength 1.35 MPa, thermal conductivity 0.43 W·m -1 K-1 .
[0028] Comparative Example 3 The difference between Example 3 and this comparative example is that step (2) is stirred in a 95 ℃ water bath for 36 h, and the rest of the experimental conditions are the same; the product prepared in this comparative example has a porosity of 81.5%, a density of 0.8436 g / cm 3 , a pore volume of 1.00 cm 3 / g, a specific surface area of 25.9 m 2 / g, a compressive strength of 1.55 MPa, and a thermal conductivity of 0.23 W·m -1 K -1 .
Claims
1. A method for preparing ZrSiO4 aerogel by sol-gel combined supercritical drying, characterized in that: The preparation process comprises the following steps: (1) the crosslinking agent is dissolved in a mixed solution of anhydrous ethanol and deionized water, and stirred and mixed uniformly; the crosslinking agent is one or more of malic acid, tartaric acid, polymaleic acid, polyacrylic acid, hexamethylenetetramine, formamide, polyethyleneimine, propylene oxide, polyvinyl alcohol, and sodium carboxymethyl cellulose; (2) the silicon source and the zirconium source are added to the mixed solution containing the crosslinking agent, and stirred uniformly to form a precursor solution; the temperature range of the raw materials during stirring is 1-80 ℃, and the stirring time is 0.1-24 h; the silicon source is one or more of tetraethyl orthosilicate, dimethyldiethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, γ-aminopropyltriethoxysilane, silica sol, and sodium silicate; the zirconium source is one or more of zirconium oxychloride, zirconyl nitrate, zirconium n-butylate, zirconium acetate, zirconium sulfate, and zirconium isopropylate; (3) the precursor solution is placed in an oven to gel, and then the obtained wet gel is soaked in ethanol for replacement; (4) the obtained wet gel is placed in a CO2 supercritical drying reaction kettle, the temperature in the reaction kettle is maintained at 4 ℃, liquid CO2 is used for replacement; the temperature in the reaction kettle is increased to make CO2 reach a supercritical state, the wet gel is dried, then the pressure is released and the dried gel is taken out; (5) the dried gel is subjected to high-temperature heat treatment to obtain ZrSiO4 aerogel.
2. A method for preparing ZrSiO4 aerogel by sol-gel combined supercritical drying according to claim 1, characterized in that: In step (1), the volume ratio of anhydrous ethanol to deionized water is 0.01:1-1:0.
01.
3. The method for preparing ZrSiO4 aerogel using a sol-gel combination and supercritical drying as described in claim 1, characterized in that: In step (2), the concentration ratio of the silicon source, the zirconium source, and the crosslinking agent in the raw materials is 1.0-2.0:1.0-2.0:0.01-4.
0.
4. The method for preparing ZrSiO4 aerogel by sol-gel combination and supercritical drying as described in claim 1, characterized in that: In step (3), the gel temperature is 30-90 ℃, and the gel time is 0.5-72 h; the wet gel is soaked in ethanol for 24-72 h.
5. The method for preparing ZrSiO4 aerogel using a sol-gel combination and supercritical drying as described in claim 1, characterized in that: In step (4), the replacement time using CO2 is 0.5-72 h; the drying time in the supercritical state is 0.1-24 h.
6. A method for preparing ZrSiO4 aerogel by sol-gel combined supercritical drying according to claim 1, characterized in that: In step (5), the heat treatment temperature is 1000-1600 ℃, and the holding time is 0.5-12 h.
Citation Information
Patent Citations
Preparation method of blocky silicon-carbon composite aerogel
CN102343285A
High-yield zirconium silicate powder synthesized by sol-gel method
CN103922354A
Preparation method of carbon / zirconium / aluminum composite aerogel material
CN105967727A
Supercritical drying method for preparing ultralow-density aero-gel and product prepared by adopting supercritical drying method
CN110553470A
High-temperature-resistant micro-nanofiber composite aerogel material and preparation method thereof
CN114870757A